Karakteristik Ekstrak Pewarna Alami Bunga Kenop (Gomphrena globosa L.) pada Perlakuan Jenis Pelarut dan Suhu Ekstraksi serta Korelasi antar Variabel - Fikri, Zainul; Wartini, Ni Made; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2020)
Globe amaranth is one of the flowers contain betacyanin that potentially used as natural dye by extracting. This research aimed to find out the characteristics of natural dye extract of globe amaranth on the treatment of solvent types and extraction temperature as well as to determine the correlation between a total of betacyanin with the yield and color intensity of the natural dye extract of globe amaranth. This experiment was designed using two factors. The first factor was solvent types consisting of aquades, ethanol 48 percent, and ethanol 96 percent. The second factor was the extraction temperature consisting of 25, 35, and  45ºC. The data analysis used a bivariate correlation test. The results showed the characteristics of the natural dye extract of globe amaranth on the treatment of the type of solvent and extraction temperature were as follows: yield of 8.65 – 16.13 percent, betacyanin total 30.01 – 185.51 mg / 100g, brightness level (L*) 12.08 – 17.09, redness level (a*) 8.19 – 10.93, and yellowish level (b*) 4.77 – 7.87.  A total of betacyanin was positively correlated with yield and the redness level (a*) with correlation coefficient value (r) 0.504 (strong) and 0.986 (very strong) and determination coefficient value (R2) 0.2541 and 0.9719, while a total of betacyanin was negatively correlated with the brightness level (L*) and the yellowish level (b*) with the correlation coefficient value (r) -0.932 (very strong) and -0.907 (very strong) and determination coefficient value (R2) 0.8679 and 0.8226. Keywords: Gomphrena globosa L., betacyanin, extraction, correlation